Capacidades perceptivo-motoras, físicas e cognitivas de idosos praticantes de Mat Pilates e Tai Chi Chuan - Oliveira, Evander Vieira de (2023)
Aging is characterized as a set of dynamic and progressive processes, in which there are morphological, functional, biochemical, motor, and psychological transformations, which lead to a loss of the individual's ability to adapt to the environment, causing greater vulnerability and greater occurrence of pathologies that end up leading to death. Thepractice of physical exercises is a necessary intervention to delay the speed with which physical and motor losses affect the elderly. Among the various possibilities of physical exercise recommended for the elderly population, the Mat Pilates (MP) and Tai Chi Chuan (TCC) stand out, which have become popular in recent years and have emerged as a way of working to improve strength and general conditioning for people of all ages. The main objective of the study is to investigate the perceptual-motor, physical and cognitive capacities of elderly practitioners of Mat Pilates (MP) and Tai Chi Chuan (TCC) and non-practitioners of physical exercises. This is an ex-post facto study involving a group of Elderly Practitioners of MP and CBT (G1) and a group of Elderly Non-Practitioners of Physical Exercise (G2). Individuals of both sexes, aged 60 years or older, practitioners of MP and CBT, and sedentary elderly who do not practice any regular physical exercise were invited to participate in the study. Anamnesis, the International Physical Activity Questionnaire (IPAQ), the Clinical-Functional Vulnerability Index-20 (IVCF-20), the Mini-Mental State Examination (MMSE), the Manual Skills Test, the Senior Fitness Test (SFT), and the Dynamometer Battery Test were used as assessment instruments. Descriptive statistics (mean, median, fashion, standard deviation, percentiles, minimum, maximum, frequencies) and inferential analysis will be used for data processing. The normality test and inferential tests will be chosen according to the number of subjects and normality distribution. For all analyses were used a significance level of 5%, tests will be performed in SPSS® version 21.0 for Windows®. As a result, a significant increase in manual skills, strength and flexibility of upper and lower limbs was obtained for the GIP, in addition to the improvement of cognitive aspects. However, there was no significant difference in the handgrip strength tests of the right and left arms and in the agility and dynamic balance test (TUG). It was concluded that the union of MP practices and TCC, in this group of elderly people, provide a significant evolution in the improvement of perceptive-motor, physical and cognitive abilities.